Randomised controlled trial comparing the intra-articular hyaluronic acid versus intra-articular steroid in osteoarthritis of knee - Tiwari, Anurag; Thora, Ankit (International Journal of Research in Orthopaedics, 2018)
Background: Osteoarthritis of knee is a chronic degenerative joint disease which leads to pain, swelling and stiffness. Intra-articular hyaluronic acid or steroids are being used for its treatment. The purpose of the present study was to assess the effect of intra articular hyaluronic acid in comparison to steroids for knee osteoarthritis. Methods: A prospective randomized study including 70 patients (121 knees) diagnosed with osteoarthritis of knee, were randomly divided into two groups: 35 patients (58 knees) were given intra-articular hyaluronic acid and 35 patients (63 knees) were given intra-articular methylprednisolone. The outcome was evaluated with knee society score (KSS) and visual analog scale (VAS) before the injection and 1, 3 and 6 months after the injection. Results: The mean KSS pain and function scores increased while VAS decreased in both the groups. All the scores showed improvement at 6 months follow up. In both the groups, the scores at 6 months were significantly better than the pre injection values, and the scores of hyaluronic acid group were significantly better compared to steroid group. Conclusions: Intraarticular hyaluronic acid seems to be better for long term pain relief and preservation of function in comparison to intraarticular steroids in osteoarthritis of knee.